Desenvolvimento de um secador de bandejas para a secagem de folhas medicinais e análise da secagem de ramos de barbatimão (Stryphnodendron adstringens) - Gardenal, Amanda Coloca (2022)
Barbatimão bark (Sryphnodendron adstringens) has been used in folk medicine for years to treat many diseases. Recently, studies indicated the potential of barbatimão leaf extract as a chemopreventive agent and as a promising candidate for the development of an antineoplastic drug for breast cancer. However, after harvesting, the leaves begin an irreversible degradation process and it is necessary to dry them to retain their properties until processing. The objective of the present study was to develop a multistage tray dryer, which operates as sequential batches, to promote material mixing and improve the use of thermal energy for drying medicinal leaves. Firstly, barbatimão branches were dried in a thick layer using 400 g of raw material, resulting in a heterogeneous product in terms of moisture. In general, the drying kinetics curves for different temperatures in oven and fixed bed operations were distinguishable; for the tray dryer, the drying curves were obtained for each stage individually, simulating the real operation by using partially dried material below each tray. It was decided to operate the dryer with 4 stages using the minimum distance between them (11.88 cm) and drying air at 60ºC and 0.4 m/s. The individual curves obtained for the 4 stages were very similar, except for the required time to reach the equilibrium moisture, which was considerably higher for superior stages. Page's model was better suited to the experimental data and, by using it, it was possible to estimate a residence time of 9.5 minutes for each stage, totaling 38 minutes for drying 100 g of barbatimão branches and obtaining a product with 10% of moisture (w.b.). The experimental data were consistent with the theoretical drying curve and the product obtained had moisture content lower than 10% (w.b.). The moisture of the final product was homogeneous, even though the mixture of material in the tray during the operation was partial, since, despite the division of the tray into three sections, the branches were concentrated in the central region, creating empty spaces. This issue was mitigated by manually vibrating all tray sections after the material was dumped. Thus, the developed dryer met the proposed objectives. The cumulative drying efficiencies of the one- and four-stages operations, drying 100 g of material, were 3.16 and 3.98% respectively, representing an increase of 25.6% for the tray dryer. The values obtained for L*, a*, b* and a*/b* for the dry products in different configurations and temperatures didn’t present statistically significant differences compared to the values of these parameters for raw leaves. The maintenance of the initial leaf color is a possible indication that the bioactives have been well preserved.